Investigation of new formulations of acrylic bone cement containing antibiotics - Matos, Ana Cristina Mendes Correia de, 1968- (2015)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2015